Design and Development of a Portable Solar-Powered Water Purification System with Automated Multi-Stage Filtration for Off-Grid Application - Mat Zian @ Mat Zin, Ahmad Faiz; Sin , Kai Sheng; Ang , Arthur Jun Rong; Rajandran, Lidhyashree Devi; Roslan, Muhammad Sufi; Johari Halim Shah, Nadira (Multidisciplinary Applied Research and Innovation, 2026)
Access to clean drinking water is a significant challenge in remote areas, where traditional treatment systems often struggle due to their reliance on electricity and high costs. This study introduces a compact solar-powered water purification system designed for sustainable and portable clean water production. The system features solar photovoltaic panels, a lithium-ion battery, and a multi-stage filtration unit with reverse osmosis and activated carbon filters to remove contaminants, including heavy metals and microorganisms. A simplified automation system with a float switch sensor and manual override helps manage pump operation and prevent overflow. An energy management system ensures a stable power supply despite varying solar conditions. Testing demonstrated significant improvements in water quality, confirming the system's effectiveness. Cost analysis suggests that this prototype is a low-cost, energy-efficient solution for rural areas. In conclusion, the solar-powered water purification system offers a practical approach to improving water access in underserved communities.